Strengthening Career Adaptability through Hardiness: A Study on New Employees - Jefriansyah, Jefriansyah; Syam, Rahmawati; Istiqamah, St. Hadjar Nurul (Jurnal Psikologi TALENTA, 2025)
Career adaptability is an essential ability required by employees to face dynamics and changes in the workplace. Employees with low career adaptability tend to experience psychological distress, difficulties in adjustment, and decreased self-confidence. This study aimed to examine the effect of hardiness on career adaptability among employees. The participants were 385 employees who were in their adaptation period, defined as having worked for less than six months, selected using convenience sampling. Career adaptability was measured using the Career Adapt-Abilities Scale (CAAS), while hardiness was measured with the Revised Dispositional Resilience Scale. Confirmatory factor analysis supported the construct validity of both instruments (CAAS: CFI = 0.93; TLI = 0.91; RMSEA = 0.074; Hardiness: CFI = 0.996; TLI = 0.992; RMSEA = 0.034). Data were analyzed using bootstrap regression. The results showed a significant effect of hardiness on career adaptability with a significance value of 0.003 (p < 0.05) and a contribution of 25.8%. Two dimensions of hardiness, namely control and commitment, had a significant effect on career adaptability, while the challenge dimension did not show a significant effect. In conclusion, the higher the level of employee hardiness, the higher their career adaptability.